Algebra

posted by .

Divide
(2x3 – x2 – 24x + 12) ÷ (2x – 1)

• Algebra -

2 x^3 – x^2 – 24 x + 12)

= (2 x^3 -24 x) - (x^2 - 12)

= 2 x (x^2-12) - 1 (x^2-12)

= (2x-1)(x^2-12)

now divide that by (2x-1) :)

• Algebra -

Thank you, I always appreciate knowing the steps that leads to the solution that I can work.

• Algebra -

You are welcome. You could have done this by long division but often you can see the factors more quickly.

Similar Questions

1. Algebra

Divide using long division: 6x3 + 19x2 + x – 10 divided by 2x -1 Divide using synthetic division: 2x3 + 2x2 + 10 divided by x + 3 PLEASE HELP!
2. algebra

Divide 48x^9-24x^3=40x 8x
3. algebra

Did I do this problem the correct way if so is there a shorter way to explain this?
4. math

Use polynomial long division to divide -4x^3 + 24x^2 – 24x + 4 by x^2 – 5x + 1
5. algebra

Use polynominal long division to divide -4x^3+24x^2-24x+4 by x^2-5x+1
6. Algebra

Divide -4x^3 + 24x^2 – 24x + 4 by x^2 – 5x + 1
7. algebra

Can someone please explain What polynomial has a graph that passes through the given points?
8. algebra

Divide 6x^3y^6 / 24x^4y^3 _______ _________ 16a^4b^2 14a^7b
9. Algebra

Divide {6x^3y^6} / {24x^4y^3} _______ _________ {16a^4b^2} {14a^7b}
10. alg2 check?

solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?

More Similar Questions